IMF Macroeconomic Research on Low-Income Countries. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2004)
Summarizes the for ward-looking analytical work program on macroeconomic issues related to the Poverty Reduction Strategy Paper approach. The program is evolving through a process that began with a technical workshop; participants from low-income countries, donors, academia, and civil society drafted guidance on selected issues and identified priority research topics. Partners, policymakers, and economic scholars are encouraged to share their perspectives and findings through respective team leaders, whose e-mail addresses are provided. The publication also summarizes IMF analytical work, and contains a bibliography of nearly 1,000 papers.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet